Human Capital, Institutions and Innovation in Sub-Saharan Africa - Stephen Oluwatobi (International Journal of Economics and Financial Issues, 2016)
This study examined the impact of human capital and institutions on innovation in Sub-Saharan Africa and clearly highlighted the relevance of the human factor in determining innovation outcomes in the Sub-Saharan African region. Using the System Generalized Method of Moments, coupled with some descriptive analyses, it was found out that human capital, as well as an enabling institutional environment, affects innovation outcomes in Sub-Saharan Africa (SSA). On the contrary, innovation outcomes in the region did not benefit from foreign investment. The study, therefore, recommends that human capital capacity be cultivated and given the enabling environment to contribute to innovation outcomes. This is expected to attract innovation-centred investments into the region.